Practical Guide to Clinical Medicine (Out of Print) - Charlie Goldberg (Association of American Medical Colleges, 2007)
Abstract This resource is a comprehensive website that offers detailed reviews of most aspects of the physical examination, including description of exam maneuvers, pictures and video of selected abnormal findings, links to other resources, and a review of history taking, presentation skills, write-ups, and clinical reasoning. This work is of particular educational relevance because it is online, is updatable, can easily incorporate images and video, and features additional links for the incorporation of other relevant works.